Exercise as an adjunct treatment for postpartum depression for women living in an inner city—A pilot study. Issue 6 (3rd June 2017) - Forsyth, Jacky; Boath, Elizabeth; Henshaw, Carol; Brown, Hannah
ABSTRACT: To examine the effectiveness of exercise in the management of postpartum depression (PPD), women living in an inner city, who were diagnosed using the Structured Clinical Interview for DSM-IV (Perinatal Version; SCID-PN), were randomly assigned to an exercise group ( N = 12) or control group ( N = 12). A focus group was carried out to explore women's views of the trial. There were no significant differences between the two groups for the SCID-PN. Although women who had engaged in the exercise viewed it positively (based on focus group data), low adherence to exercise meant that significant improvements in PPD were not found.